Plant Genomics - You, Frank M. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue contains 28 papers covering a wide range of topics related to plant genomics and genetics. The papers utilize a variety of genomic tools and techniques to explore topics such as identification of quantitative trait loci associated with flax seed yield and oil quality, mucilage and hull content in flax seeds, and genomic prediction for pasmo resistance in flax. Other papers focus on the identification and characterization of specific genes, such as the EXO70 gene family in wheat and related species, hydroxycinnamoyl transferase in tea plants, and the WRKY transcription factor GmWRKY12 in soybeans. Several papers examine gene expression and regulation in response to abiotic stress, such as drought and salt tolerance in moso bamboo, and the response to chilling in bell peppers. Other topics include genetic diversity analysis of crested wheatgrass, genome-wide analysis of chitin-binding protein gene family in peppers, and genome-wide bioinformatics analysis of MAPK gene family in kiwifruit. Overall, this Special Issue provides a comprehensive view of the current state of plant genomics research, showcasing the diversity of approaches and tools being used to better understand and improve crop plants.